Destruction of emergent tuff cones in Faial Island, Azores: influence of tectonics and marine erosion - Pedrazzi, Dario; Zanon, V.; Pimentel, A.; Tempera, F. (2020)
8th International MAAR CONFERENCE, Kamchatka, 24-30 August 2020 The island of Faial is the westernmost of the central islands of the Azores archipelago (North Atlantic Ocean), and is located east of the Mid-Atlantic Ridge. The Azores are in a unique geodynamic setting at the triple junction of the North-American, Eurasian and Nubia lithospheric plates (Searle, 1980; Madeira and Ribeiro, 1990; Vogt and Jung, 2004) (Fig. 1a) D.P. is grateful for his Juan de la Cierva (IJCI-2016-30482) contract.